Ekstraksi Polifenol Total dari Umbi Bawang Dayak (Eleutherine bulbosa [Mill.] Urb.) menggunakan Metode Lactic Acid-Sucrose based Microwave Assisted Extraction - Kurnya Kurnya; Hajrah Hajrah; Islamudin Ahmad (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2019)
Dayak Onion (Eleutherine bulbosa [Mill.] Urb.) It is a plant that grows in Indonesia precisely in the Kalimantan area and has traditionally efficacious in curing various diseases such as diabetes mellitus, hypertension, breast cancer, cholesterol-lowering, and stroke. This study aims to determine the effect of using the lactic acid-sucrose based microwave-assisted extraction (MAE) method to extract total polyphenols from Dayak onion tubers (Eleutherine bulbosa [Mill.] Urb.). Dry samples were extracted using a lactic-sucrose acid (green solvent) solvent in the ratio of 1: 1, 2: 1, and 3: 1 g/g with 50% microwave strength for 10 minutes with a ratio of samples and solvents of 1:10 g /mL. Extracts that have been obtained then determined the total polyphenol levels using a UV-VIS spectrophotometer at a wavelength of 791 nm. Based on the results of the study, it was obtained the levels of polyphenols from each condition of the solvent used in the sample that is 28.73 mg GAE/g sample ( 1: 1 g/g solvent); 20.2 mg GAE/g sample ( 2:1 g/g solvent); 36.35 mg GAE/g sample ( 3:1 g/g solvent). From this study, it can be concluded that the MAE method can be used to extract polyphenol compounds from Dayak bulbs.